Preparation method of high-flame-retardant sound-insulation composite aerogel material with oriented lamellar structure

By introducing inorganic nanoparticles into the organic lamellar structure, a composite aerogel material with an oriented lamellar structure is formed, which solves the problem of difficulty in achieving high heat insulation, high sound insulation and flame retardancy in the existing technology, and achieves efficient insulation. Thermal, acoustic and flame retardant properties.

CN119350703AInactive Publication Date: 2025-01-24ANHUI AGRICULTURAL UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411665199.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

It is difficult for the prior art to introduce inorganic nanoparticles into the organic sheet structure to realize high heat insulation and high sound insulation flame-retardant composite aerogel materials.

Method used

By dissolving the chitosan (CS) in a mixed solution of ion water and acetic acid, and the calcium carbonate (CACO3) is evenly dispersed into the CS solution through the ultrasonic dispersing process to form a common phase solution. Then through the two -way freezing technology and frozen drying process, the directional growth of the ice crystal is arranged in an orderly manner to form a high -flame and sound insulation composite gas gel material with the structure of the orientation layer.

Benefits of technology

A composite gas gel material with high flame -retardant, high -fidelity and high sound insulation, has stable mechanical properties, excellent thermal insulation performance, good sound insulation performance and prominent flame retardant performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350703A_ABST
    Figure CN119350703A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-flame-retardant sound-insulation composite aerogel material with an oriented lamellar structure, which is characterized by comprising the following steps: step 101, adding chitosan (CS) into deionized water and a small amount of acetic acid to obtain a chitosan solution, and heating and stirring; step 102, uniformly dispersing CaCO3 into the CS solution through an ultrasonic dispersion process to obtain a CS / CaCO3 homogeneous solution; 103, the obtained CS / CaCO3 homogeneous solution is poured into a polytetrafluoroethylene mold and placed on a 20-degree slope cooling plate to be frozen; and step 104, freeze-drying the frozen sample in a vacuum freeze-drying machine to finally obtain the high-flame-retardant sound-insulation composite aerogel material (FINCC) with the oriented lamellar structure. Compared with the existing aerogel material, the composite aerogel material disclosed by the invention has stable mechanical properties, excellent heat insulation performance, good sound insulation performance and outstanding flame retardant property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite aerogel materials, in particular to a method for preparing a highly flame-retardant and sound-insulating composite aerogel material with an oriented sheet structure. Background Art

[0002] As a porous solid material, aerogel has extremely low density and high porosity, which makes it excellent in thermal insulation. Its thermal conductivity is extremely low, so it can provide excellent thermal insulation capabilities. Aerogels are usually divided into two categories, organic aerogels and inorganic aerogels, each with its own advantages and disadvantages. They cannot have the advantages of both inorganic and organic materials, which limits their application. Therefore, how to prepare aerogels that have the advantages of both inorganic and organic materials is of great significance, but it still faces great challenges.

[0003] Organic aerogels have the advantages of light weight, excellent thermal insulation performance, good sound insulation performance, easy installation, etc. However, organic aerogels have poor flame retardancy, are easily ignited, and release a large amount of harmful gases when burned. The thermal insulation performance of inorganic aerogels is usually lower than that of organic aerogels, and their high brittleness and narrow mechanical construction window severely limit the application of inorganic aerogels. The composite of organic materials and inorganic materials is expected to achieve both high flame retardancy and high thermal insulation, but the interface compatibility between inorganic and organic materials is poor. In addition, oriented lamellar structures are often used to design and increase the thermal insulation performance of materials. The ordered lamellar structure is stressed layer by layer, which can significantly improve the mechanical properties of the material.

[0004] Therefore, how to introduce inorganic nanoparticles into the organic layer structure is expected to achieve flame-retardant composite aerogel materials with high thermal insulation and sound insulation, but it still faces great challenges. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a highly flame retardant and sound insulating composite aerogel material with an oriented sheet structure, so as to solve the problems in the prior art, improve the interface compatibility between organic and inorganic substances and prepare a composite aerogel material with high flame retardancy, high thermal insulation and high sound insulation.

[0006] The present invention provides a method for preparing a highly flame-retardant and sound-insulating composite aerogel material having an oriented sheet structure, comprising the following steps:

[0007] Step 101, adding CS to deionized water and a small amount of acetic acid to obtain a chitosan solution and heating and stirring;

[0008] Step 102, uniformly dispersing CaCO3 into the CS solution by ultrasonic dispersion process to obtain a CS / CaCO3 homogeneous solution;

[0009] Step 103, pouring the obtained CS / CaCO3 homogeneous solution into a polytetrafluoroethylene mold and placing it on a 20-degree slope cooling plate for freezing;

[0010] Step 104, placing the frozen sample into a vacuum freeze dryer for freeze drying to finally obtain FINCC.

[0011] In the method for preparing a highly flame-retardant and sound-insulating composite aerogel material with an oriented sheet structure as described above, preferably, the amount of CS used in step 101 is 2 g.

[0012] In the method for preparing a highly flame-retardant and sound-insulating composite aerogel material with an oriented sheet structure as described above, preferably, the amount of acetic acid used in step 101 is 1 g.

[0013] The method for preparing a highly flame-retardant and sound-insulating composite aerogel material with an oriented sheet structure as described above, wherein, preferably, the mass fraction of the CS solution in step 101 is 2 wt %, relative to 2 g of CS, the amount of acetic acid used is 1 g, and the amount of deionized water used is 97 g.

[0014] In the method for preparing a highly flame-retardant and sound-insulating composite aerogel material with an oriented sheet structure as described above, preferably, the stirring and mixing in step 101 is performed by stirring for 12 hours using a magnetic stirrer.

[0015] In the method for preparing the highly flame-retardant and sound-insulating composite aerogel material with an oriented sheet structure as described above, preferably, the heating temperature in step 101 is 60°C.

[0016] In the method for preparing a highly flame-retardant and sound-insulating composite aerogel material with an oriented sheet structure as described above, preferably, the mass of CaCO3 added in step 102 is 20 g relative to 2 g of CS.

[0017] As described above, in the method for preparing a highly flame-retardant and sound-insulating composite aerogel material with an oriented sheet structure, preferably, in step 102, the ultrasonic time is 30 minutes, the ultrasonic frequency is 30 kHz, and the power is 50 W.

[0018] As described above, in the method for preparing a highly flame-retardant and sound-insulating composite aerogel material with an oriented sheet structure, preferably, the temperature of the cooling plate in step 103 is -196°C, and the cooling time is 40 minutes.

[0019] The method for preparing a highly flame-retardant and sound-insulating composite aerogel material with an oriented sheet structure as described above, wherein preferably, the freeze-drying time in step 104 is 72 hours.

[0020] Compared with the prior art, the composite aerogel material of the present invention has stable mechanical properties, excellent heat insulation properties, good sound insulation properties, and outstanding flame retardant properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is a scanning electron microscope image of FINCC-10 obtained in Example 1;

[0022] Figure 2 is the pressure diagram of FINCC-10 obtained in Example 1;

[0023] Figure 3 is a stress-strain curve diagram of different deformation amounts of compression in Example 1;

[0024] Figure 4 is a thermal infrared image of the FINCC-10 obtained in Example 1 on a hot stage after being cut into different shapes;

[0025] Figure 5 is the change of thermal conductivity coefficient of FINCC-10 obtained in Example 1 after compression and different deformation;

[0026] Figure 6 is the limiting oxygen index of FINCC-10 in Example 1, FINCC-5 in Example 2, FINCC-1 in Example 3, and FINCC-0 in the comparative example;

[0027] Figure 7 is a graph of heat release and smoke generation of FINCC-10 in Example 1 and FINCC-0 in the comparative example;

[0028] Figure 8 It is a test of the sound insulation performance of FINCC-10 prepared in Example 1;

[0029] Fig. 9 This is a picture of a mini car model assembled with FINCC-10 in the application example;

[0030] Fig.10 It is the thermal insulation and sound insulation performance in actual application in the application example. DETAILED DESCRIPTION

[0031] The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, but should not be construed as limiting the present invention.

[0032] The present invention provides a method for preparing a composite aerogel material with high flame retardancy and high sound insulation by introducing inorganic nanomaterials into an organic sheet structure. The preparation method comprises:

[0033] First, chitosan (CS) was dissolved in a mixture of water and a small amount of acetic acid to obtain a CS solution, and then

[0034] Calcium carbonate (CaCO3) is dispersed into CS solution to obtain a uniformly dispersed (CS / CaCO3) solution. Finally, FINCC is obtained through bidirectional freezing technology and freeze-drying process. Specifically, due to the presence of a large number of functional groups such as hydroxyl and amino groups in CS, which can react with metal nanoparticles, CaCO3 can be evenly dispersed into CS solution through ultrasonic dispersion process to obtain a homogeneous solution, and then bidirectional freezing is performed by placing it on a special cold source. The ice crystals that grow directionally during the bidirectional freezing process can squeeze the CS solution to arrange it in an orderly pattern, and then the ice crystals in the sample are extracted through the freeze-drying process to obtain an ordered lamellar porous material, namely FINCC. Benefiting from the rigidity of CaCO3 itself and the stability of the lamellar structure, the prepared FINCC exhibits excellent mechanical properties, which provides a good mechanical construction window for it as a composite aerogel material. There is a large amount of air in the gaps of the oriented lamellar structure, which interrupts the heat transfer path of the solid, thereby making FINCC have excellent thermal insulation properties. In addition, the oriented sheet structure can also effectively reflect sound, and the sound insulation of FINCC in the mid-frequency band exceeds 40dB. More importantly, the introduction of calcium carbonate makes FINCC have excellent flame retardant properties, and its limiting oxygen index can reach 99.12. In summary, the above properties of FINCC show that the composite aerogel material of this invention has excellent performance.

[0035] In the embodiment provided by the present invention, the preparation method of the highly flame-retardant and sound-insulating composite aerogel material having an oriented sheet structure comprises the following steps:

[0036] Step 101, adding CS to deionized water and a small amount of acetic acid to obtain a CS solution and heating and stirring the solution;

[0037] Step 102: Disperse CaCO3 uniformly into the CS solution by ultrasonic dispersion process to obtain a CS / CaCO3 homogeneous solution.

[0038] Step 103: Pour the obtained CS / CaCO3 homogeneous solution into a polytetrafluoroethylene mold and place it on a 20-degree slope cooling plate for freezing.

[0039] Step 104, placing the frozen sample into a vacuum freeze dryer for freeze drying to finally obtain FINCC.

[0040] In a feasible implementation manner, the amount of CS in step 101 is 2 g, the amount of acetic acid in step 101 is 1 g, the mass fraction of the CS solution in step 101 is 2 wt %, relative to 2 g of CS, the amount of acetic acid is 1 g, the amount of deionized water is 97 g, the stirring and mixing in step 101 is stirring for 12 h using a magnetic stirrer, the heating temperature in step 101 is 60° C., the mass of CaCO3 added in step 102 is 20 g relative to 2 g of CS, the ultrasonic time in step 102 is 30 minutes, the ultrasonic frequency is 30 kHz, and the power is 50 W, the temperature of the cooling plate in step 103 is -196° C., the cooling time is 40 minutes, and the freeze-drying time in step 104 is 72 h.

[0041] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] Example 1

[0043] This embodiment discloses a method for preparing a composite aerogel material FINCC-10, comprising the following steps:

[0044] 1) 2 g of CS was added to 97 g of ionized water, and then 1 g of acetic acid was added, followed by stirring at 60° C. for 12 hours to obtain a CS solution.

[0045] 2) 20 g of CaCO3 was uniformly dispersed into the CS solution by ultrasonic dispersion process, with ultrasonic power of 60 kW and time of 30 minutes to obtain a CS / CaCO3 homogeneous solution.

[0046] 3) The obtained CS / CaCO3 homogeneous solution was poured into a polytetrafluoroethylene mold and placed on a 20-degree slope cooling plate for freezing. The obtained CS / CaCO3 homogeneous solution was poured into a polytetrafluoroethylene mold and placed on a 20-degree slope cooling plate with a temperature of -196°C for freezing for 50 minutes.

[0047] 4) The frozen sample was placed in a vacuum freeze dryer and freeze-dried for 72 hours to obtain FINCC-10.

[0048] Example 2

[0049] This embodiment discloses a method for preparing a composite aerogel material FINCC-5, comprising the following steps:

[0050] 1) 2 g of CS was added to 97 g of ionized water, and then 1 g of acetic acid was added, followed by stirring at 60° C. for 12 hours to obtain a CS solution.

[0051] 2) 10 g of CaCO3 was uniformly dispersed into the CS solution by ultrasonic dispersion process, with ultrasonic power of 50 kW and time of 30 minutes to obtain a CS / CaCO3 homogeneous solution.

[0052] 3) The obtained CS / CaCO3 homogeneous solution was poured into a polytetrafluoroethylene mold and placed on a 20-degree slope cooling plate for freezing. The obtained CS / CaCO3 homogeneous solution was poured into a polytetrafluoroethylene mold and placed on a 20-degree slope cooling plate with a temperature of -196°C for freezing for 50 minutes.

[0053] 4) The frozen sample was placed in a vacuum freeze dryer and freeze-dried for 72 hours to obtain FINCC-5.

[0054] Example 3

[0055] This embodiment discloses a method for preparing a composite aerogel material FINCC-1, comprising the following steps:

[0056] 1) 2 g of CS was added to 97 g of ionized water, and then 1 g of acetic acid was added, followed by stirring at 60° C. for 12 hours to obtain a CS solution.

[0057] 2) 2 g of CaCO3 was uniformly dispersed into the CS solution by ultrasonic dispersion process, with ultrasonic power of 40 kW and time of 30 minutes to obtain a CS / CaCO3 homogeneous solution.

[0058] 3) The obtained CS / CaCO3 homogeneous solution was poured into a polytetrafluoroethylene mold and placed on a 20-degree slope cooling plate for freezing. The obtained CS / CaCO3 homogeneous solution was poured into a polytetrafluoroethylene mold and placed on a 20-degree slope cooling plate with a temperature of -196°C for freezing for 50 minutes.

[0059] 4) The frozen sample was placed in a vacuum freeze dryer and freeze-dried for 72 hours to obtain FINCC-1.

[0060] Comparative Example

[0061] This embodiment discloses a method for preparing a comparative example of a composite aerogel material, comprising the following steps:

[0062] 1) 2 g of CS was added to 97 g of ionized water, and then 1 g of acetic acid was added, followed by stirring at 60° C. for 12 hours to obtain a CS solution.

[0063] 2) The obtained CS solution was poured into a polytetrafluoroethylene mold and placed on a 20-degree slope cooling plate for freezing; the obtained CS / CaCO3 homogeneous solution was poured into a polytetrafluoroethylene mold and placed on a 20-degree slope cooling plate at a temperature of -196°C for freezing for 50 minutes.

[0064] 3) The frozen sample was placed in a vacuum freeze dryer and freeze-dried for 72 hours to obtain FINCC-0.

[0065] Performance Testing

[0066] The FINCC-10 prepared in Example 1 was placed in a S6800 scanning electron microscope to obtain its microscopic morphology as shown in FIG. Figure 1 As shown in the figure, it can be seen that FINCC-10 exhibits an ordered lamellar porous structure. Benefiting from its special lamellar structure, it has excellent thermal insulation, flame retardancy, sound insulation and mechanical properties.

[0067] Place a 100g weight on FINCC-10. Figure 2 As shown, it can be seen that the height of FINCC-10 does not change under the pressure of a 100g weight, indicating its excellent mechanical properties.

[0068] The mechanical properties of FINCC-10 under different compressions were tested using an electronic universal testing machine. The speed was set to 5 mm min-1 to obtain the stress-strain curves, as shown in the figure. Figure 3 As shown, it can be seen that FINCC-10 has a wide construction mechanics window and can withstand the inevitable deformation during construction and use.

[0069] The thermal infrared images of FINCC-10 cut into different shapes and placed on a 100℃ hot stage are shown in the figure below. Figure 4 As shown, it can be seen that FINCC-10 has excellent processing performance and thermal insulation performance.

[0070] The thermal conductivity of FINCC-10 in Example 1, FINCC-5 in Example 2, FINCC-1 in Example 1 and FINCC-0 in the comparative example was tested using a multifunctional thermal conductivity meter. Figure 5 As shown, it can be seen that with the increase of the amount of nano-calcium carbonate, the thermal conductivity of FINCC gradually increases, but it is still a high-efficiency thermal insulation material.

[0071] The FINCC-10 in Example 1, the FINCC-5 in Example 2, the FINCC-1 in Example 3 and the FINCC-0 in the comparative example were cut into a size of 100 mm x 10 mm x 10 mm and placed in a fully automatic limiting oxygen index instrument to test the minimum oxygen concentration required for the combustion of the samples. The limiting oxygen index is as follows: Figure 6As shown, it can be seen that with the increase of nano calcium carbonate, the limiting oxygen index of the sample is constantly increasing. The limiting oxygen index of FINCC-10 in Example 1 is as high as 99.12, reaching the non-flammable level.

[0072] The FINCC-10 in Example 1 and the FINCC-0 in the comparative example were cut into a size of 100 mm x 20 mm x 4 mm, and then the heat release and smoke generation were tested. The combustion radiation intensity was set to 30 kW·m -2 The test results are as follows Figure 7 As shown, it can be seen that the heat release and smoke generation of FINCC-10 in Example 1 are greatly reduced compared with those of the comparative example FINCC-0, showing its excellent flame retardant performance.

[0073] The sample in Example 1 was cut into a size of 29 mm in height and 20 mm in height, and then placed in a sound-resistance tube for testing. The test results of the sound insulation of FINCC-10 at different frequencies are as follows: Figure 8 As shown, it shows that FINCC-10 has excellent sound insulation performance in the mid-frequency band.

[0074] The FINCC prepared by the method of the present application can be used as a composite aerogel material in the automotive field. The FINCC-10 in Example 1 is cut into cuboids of different shapes, and then the cuboids are spliced ​​into a simple imitation car interior model, such as Fig. 9 As shown, the model is then placed in a 50-degree environment for baking, and the temperature change of the simple simulated car interior model over time is recorded. Use a mobile phone to emit sounds of different frequencies, and then use a multi-function noise meter to test its sound insulation, its internal temperature change, and its sound insulation. Fig.10 As shown, it can be seen that after being placed in an environment of 50°C for 1 hour, its internal temperature finally stabilizes at 37°C, indicating its excellent thermal insulation performance. Its sound insulation data graph shows that FINCC-10 has excellent sound insulation performance in the mid-frequency band.

[0075] The above describes in detail the structure, features and effects of the present invention based on the embodiments shown in the drawings. The above is only a preferred embodiment of the present invention, but the present invention is not limited to the scope of implementation shown in the drawings. Any changes made according to the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which still do not exceed the spirit covered by the description and drawings, should be within the protection scope of the present invention.

Claims

1. A method for preparing a highly flame-retardant and sound-insulating composite aerogel material having an oriented sheet structure, characterized in that: The following steps are involved: Step 101, adding CS to deionized water and a small amount of acetic acid to obtain a chitosan solution and heating and stirring; Step 102, uniformly dispersing CaCO3 into the CS solution by ultrasonic dispersion process to obtain a CS / CaCO3 homogeneous solution; Step 103, pouring the obtained CS / CaCO3 homogeneous solution into a polytetrafluoroethylene mold and placing it on a slope cooling plate at 20° C. for freezing; Step 104: Place the frozen sample into a vacuum freeze dryer for freeze drying to obtain FINCC.

2. The method for preparing a highly flame-retardant and sound-insulating composite aerogel material having an oriented sheet structure according to claim 1, characterized in that: The amount of CS used in step 101 is 2 g.

3. The method for preparing a highly flame-retardant and sound-insulating composite aerogel material having an oriented sheet structure according to claim 1, characterized in that: The amount of acetic acid used in step 101 is 1 g.

4. The method for preparing a highly flame-retardant and sound-insulating composite aerogel material having an oriented sheet structure according to claim 1, characterized in that: In step 101, the mass fraction of the CS solution is 2 wt %. Relative to 2 g of CS, the amount of acetic acid used is 1 g, and the amount of deionized water used is 97 g.

5. The method for preparing a highly flame-retardant and sound-insulating composite aerogel material having an oriented sheet structure according to claim 1, characterized in that: The stirring and mixing in step 101 is performed by stirring for 12 hours using a magnetic stirrer.

6. The method for preparing a highly flame-retardant and sound-insulating composite aerogel material having an oriented sheet structure according to claim 1, characterized in that: The heating temperature in step 101 is 60°C.

7. The method for preparing a highly flame-retardant and sound-insulating composite aerogel material having an oriented sheet structure according to claim 1, characterized in that: The mass of CaCO3 added in step 102 is 20 g relative to 2 g of CS.

8. The method for preparing a highly flame-retardant and sound-insulating composite aerogel material with an oriented sheet structure according to claim 1, characterized in that: In step 102, the ultrasonic time is 30 minutes, the ultrasonic frequency is 30 kHz, and the power is 50 W.

9. The method for preparing a highly flame-retardant and sound-insulating composite aerogel material with an oriented sheet structure according to claim 1, characterized in that: In step 103, the temperature of the cooling plate is -196°C, and the cooling time is 40 minutes.

10. The method for preparing a highly flame-retardant and sound-insulating composite aerogel material with an oriented sheet structure according to claim 1, characterized in that: The freeze drying time in step 104 is 72 hours.

Citation Information

Patent Citations

  • Plant polysaccharide heat insulation aerogel material and preparation method

    CN108285549A

  • Chitin-chitosan-based bi-crosslinking aerogel and preparation method thereof

    CN115536896A

  • Ultrahigh-flame-retardant external wall thermal insulation material as well as preparation method and application thereof

    CN118047977A